An Analysis of Sustainability Status of Informal Settlements in Ardebil - jila farzaneh sadat zaranji; Dr. mohammad hasan yazdani (جغرافیا و آمایش شهری منطقه‌ای, 2019)
Sustainable urban development is based on the principle that a city within the neighborhood is formed and based on it, hence, neighborhood development is considered as a key step toward sustainable development. Among the most important reflections of contemporary urbanization is the emergence and spread of vulnerable neighborhoods (informal housing) in the center or around cities, including Ardabil. In this city, informal settlements can be considered as forgotten and unplanned areas compared to other urban neighborhoods that are sustainably frailing. Although instability is a long-standing problem and an obvious problem in informal housing, it is not possible to manage and improve the situation at the same time. thus, recognizing the degree of instability and weakness through comparative and reliance comparisons Different models of decision making between the total of these neighborhoods can help to improve the performance and decision making of urban managers in accordance with the priority of intervention in these areas in order to empower them in the direction of sustainable urban development. Therefore, the purpose of this study was to analyze and compare the comparative situation of instability in 15 informal settlements in Ardebil with emphasis on neighborhood sustainability criteria and prioritize them for future planning. This research is applied in terms of purpose and in terms of method is descriptive-analytical one. Required data are collected through field methods. The statistical population of the research is in accordance with the 15 neighborhoods of informal settlements in Ardebil. To assess the stability of the studied neighborhoods, the relevant indices were used using the entropy of weighing method and the target areas by using decision-making techniques. Finally, for coplanqui integration technique, the final priority was used. And finally, Terrible Maps for better representations using ArcGIS software. Based on the measures taken and the results of implementing various decision making techniques in terms of sustainable metrics, Salman Abad's neighborhood ranked first and Iran-Abad neighborhood with the lowest score. Therefore, developmental planning in appropriate with the strengths and priorities of each neighborhood seems necessary.